MICROECOLOGICAL LANDSCAPE OF DIFFERENT BIOTOPES IN CHILDREN LIVING IN IRKUTSK REGION - S. M. Popkova; E. B. Rakova; E. L. Kichigina; U. M. Nemtchencko; Eu. P. Dzhioyev (Acta Biomedica Scientifica, 2012)
Intestinal, nasopharyngeal microbiocenoses peculiarities and bifidobacteria species composition in children living in the Irkutsk region industrial cities under existing technogenic loading conditions have been studied. Major microbiocenosis variants in children living in the cities with the different levels of the atmospheric air pollution have been determined